Negotiative Coexistence of the Wahabi Movement and Religious Moderation in East Lombok - Azizah, Lutfatul; Zuhrupatul Jannah; Halimatuzzahro (Jurnal Sosiologi Agama, 2025)
This research was conducted in three villages in East Lombok, namely Suralaga, Bagik Nyaka, and Kalijaga, to understand the phenomenon of the Wahabi movement and religious moderation in society. The main reason for this research is the increasing conflict due to differences in religious understanding triggered by the exclusivity of the Wahabi group. This research aims to analyze the pattern of social interaction and values of religious moderation between Wahabi groups and cultural Islamic society. With a qualitative approach, data were collected through in-depth interviews, observation, and documentation. The results showed that the exclusivity of the Wahabi group led by its elite became a trigger for conflict, while grassroots worshipers showed the potential to accept the values of moderation. Mosques and education are the main media for the spread of Wahabi ideology. However, efforts to strengthen religious moderation can be done by encouraging tolerance and understanding across groups. The conclusion of this research emphasizes the importance of religious moderation strategies to create harmony amid religious differences.